Novel insight into the genetic signatures of altitude adaptation related body composition in Tibetans - Li, Xuguang; Xu, Shilin; Li, Xuemei; Wang, Yuhe; Sheng, Yemeng; Zhang, Hengxun; Yang, Wei; Yuan, Dongya; Jin, Tianbo; He, Xue (Frontiers in Public Health, 2024)
Background: The Tibetan population residing in high-altitude (HA) regions has adapted to extreme hypoxic environments. However, there is limited understanding of the genetic basis of body compositions in Tibetan population adapted to HA. Methods: We performed a genome-wide association study (GWAS) to identify genetic variants associated with HA and HA-ralated body composition traits. A total of 755,731 single nucleotide polymorphisms (SNPs) were genotyped using the precision medicine diversity array from 996 Tibetan college students. T-tests and Pearson correlation analysis were used to estimate the association between body compositions and altitude. The mixed linear regression identified the SNPs significantly associated with HA and HA-related body compositions. LASSO regression was used to screen for important SNPs in HA and body compositions. Results: Significant differences were observed in lean body mass (LBW), muscle mass (MM), total body water (TBW), standard weight (SBW), basal metabolic rate (BMR), total protein (TP), and total inorganic salt (Is) in different altitudes stratification. We identified three SNPs in EPAS1 (rs1562453, rs7589621 and rs7583392) that were significantly associated with HA (p < 5×10-7). GWAS analysis of 7 HA-related body composition traits, we identified 14 SNPs for LBM, 11 SNPs for TBW, 15 SNPs for MM, 16 SNPs for SBW, 9 SNPs for BMR, 12 SNPs for TP, and 26 SNPs for Is (p < 5.0×10-5). Conclusions: These findings provide insight into the genetic basis of body composition in Tibetan college students adapted to HA, and lay the foundation for further investigation into the molecular mechanisms underlying HA adaptation.